A propeptide‐independent protease from Tannerella sp.6_1_58FAA_CT1 displays trypsin‐like specificity. (7th October 2016) - Song, Qitao; Zhang, Xiaoyue; Li, Na; Shen, Jie; Cheng, Jiansong
Abstract : Despite the absence of any homologs of Tannerella forsythia KLIKK proteases in Tannerella sp.6_1_58FAA_CT1, the strain possesses a putative cysteine protease (G9S4N1) closely related to RgpB of Porphyromonas gingivalis . G9S4N1 lacks obvious propeptide that behaves as inhibitor of proteases and was proven to be a propeptide‐independent protease. Unlike RgpB, which exclusively cleaves ArgXaa bonds, G9S4N1 exhibits both arginine‐ and citrulline‐specific activities. Mutations of Asp177, a potential P1‐Arg binding site, to uncharged or positively charged residues did not alter the substrate specificity of G9S4N1 significantly. Moreover, a group of arginine‐specific proteases from different species including porcine trypsin, bovine thrombin, and a trypsin‐like serine protease of dengue 2 virus CF40‐Gly‐NS3pro185 also display different specificity toward citrulline residue, suggesting that citrulline‐modified protein might have different roles and destiny in biological processes involving various proteases.